Meat-Producing Ability of Two Autochthonous Chicken Breeds Under Traditional and Semi-Intensive Conditions - András Gáspárdy; Rita Bélley; Ildikó Barta (Agriculture)
The old Hungarian poultry breeds are the hidden reserves of the Carpathian Basin’s agriculture. The aim of this study was to examine the slaughter weight, carcass merit, and certain meat properties of two of them: the Partridge-colored Hungarian Chicken (PC) and the White Transylvanian Naked-neck Chicken (TN) under semi-intensive and traditional fattening conditions. Test slaughtering of chickens was conducted at 12th and 18th weeks of age. The eviscerated body weight (and the weight of cuts) of the PC (1140 g) and the cockerels of both breeds (1148 g) was larger than that of TN (878 g) and pullets (870 g). The farming system did not influence the carcass composition. At the same time, the pullets were characterized with larger values (p < 0.001) in regards to, for example, the breast–whole leg (0.81:1), breast fillet–thigh fillet (1.29:1), breast fillet–breast bone proportion (2.40:1) in comparison to the cockerels (0.7:1, 1.10:1 and 2.17:1, respectively). Examinations of meat quality revealed that the pH-value of the thigh (5.73 vs. 5.83) and breast meat (6.21 vs. 6.43) of the PC was significantly lower. However, the lightness (L*) of breast fillet was higher (55.2) than that in the TN (49.9). In addition, the yellowness (b*) value of the breast meat and breast skin was significantly higher in the PC, but the redness (a*) of the breast skin was higher in the TN. Results showed that the farming system affects these values, too. Accordingly, the yellowness (b*) of breast meat, breast skin, thigh meat, and thigh skin was significantly higher in the traditional group. The PC showed more satisfactory results in poultry production today. However, the reddish meat of the TN should be emphasized, which is excellent and appropriate in traditional agriculture. It is argued that the indigenous chicken breeds should be supported for the chicken meat trade regardless of their competitiveness.